Tetramethylpyrazine (TMP) protects rats against acute pancreatitis through NF-κB pathway. Issue 1 (1st January 2019) - Chen, Longying; Chen, Yongjun; Yun, Hao; Jianli, Zhang
ABSTRACT: Acute pancreatitis (AP) is a digestive disease characterized by pancreatic inflammation. Tetramethylpyrazine (TMP) has been effectively used to ameliorate the damage on intestinal mucosa injury in rats with acute necrotizing pancreatitis (ANP). We aim to study the protective effect of TMP on caerulein-induced AP and to explore the possible mechanism. The mice randomized into control and different experimental groups. AP was induced in mice by 6-hourly intraperitoneal (i.p) injections of caerulein (50 μg/kg at 1 h interval). TMP (i.p, 10 mg/kg, 1 h interval) was administered 3 h before caerulein injection. Administration of TMP attenuated the severity of AP as shown by the histopathology, reduced serum amylase activity and pro-inflammatory cytokines TNF-α and IL-6. Further, TMP enhances the beneficial effect by reducing caerulein-induced NF-κB activation and inducing cell apoptosis in pancreas. Therefore, inhibition of nuclear factor-kappa B(NF-κB) signals by TMP represents a potential therapeutic strategy for the treatment of acute pancreatitis. Graphical abstract: uf0001